PD Fuzzy Logic with Non-collocated PID Approach for Vibration Control of Flexible Joint Manipulator - Mohd Ashraf, Ahmad; Mohd Helmi, Suid; Mohd Syakirin, Ramli (2010)

(untitled)
The increased complexity of the dynamics of robots manipulator considering joint elasticity makes conventional model-based control strategies complex and difficult to synthesize. This paper presents investigations into the development of PD type Fuzzy Logic Control (FLC) with non-collocated Proportional Integral Derivative (PID) for trajectory tracking and vibration control of a flexible joint manipulator. To study the effectiveness of the controllers, a PD type Fuzzy Logic Controller is developed for tip angular position control of a flexible joint manipulator. This is then extended to incorporate a non-collocated PID Controller for vibration reduction of the flexible joint system. Simulation results of the response of the flexible joint manipulator with the controllers are presented in time and frequency domains. The performances of the non-collocated PID control schemes are examined in terms of input tracking capability, level of vibration reduction and time response specifications. Finally, a comparative assessment of the control techniques is presented and discussed.